2011
DOI: 10.1088/0953-2048/24/8/085018
|View full text |Cite
|
Sign up to set email alerts
|

Advanced titania buffer layer architectures prepared by chemical solution deposition

Abstract: Chemical solution deposition (CSD) was used to grow high-quality (100) oriented films of SrTiO3 (STO) on CSD CaTiO3 (CTO), Ba0.1Ca0.9TiO3 (BCT) and STO seed and template layers. These template films bridge the lattice misfit between STO and the nickel–tungsten (NiW) substrate, assisting in dense growth of textured STO. Additional niobium (Nb) doping of the STO buffer layer reduces oxygen diffusion which is necessary to avoid undesired oxidation of the NiW. The investigated templates offer suitable alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…Here, the 50 µV-3f criterion is used which is comparable to the standard 1 µV resistive voltage drop over 1 cm length. [30] One of the main shortcomings of YBCO as a superconductor material is the dependence of the Jc on the magnetic field strength and orientation in high-field applications, like wind mill energy in which the superconductor is coated as a coil. [31] It has been shown that these problems can be circumvented by the introduction of various structural and morphological defects in the superconducting layer, so-called artificial pinning centers (APCs).…”
Section: Applications High Temperature Yba2cu3o7-x Superconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the 50 µV-3f criterion is used which is comparable to the standard 1 µV resistive voltage drop over 1 cm length. [30] One of the main shortcomings of YBCO as a superconductor material is the dependence of the Jc on the magnetic field strength and orientation in high-field applications, like wind mill energy in which the superconductor is coated as a coil. [31] It has been shown that these problems can be circumvented by the introduction of various structural and morphological defects in the superconducting layer, so-called artificial pinning centers (APCs).…”
Section: Applications High Temperature Yba2cu3o7-x Superconductorsmentioning
confidence: 99%
“…[31] It has been shown that these problems can be circumvented by the introduction of various structural and morphological defects in the superconducting layer, so-called artificial pinning centers (APCs). [30] We want to use carefully chosen ceramic NPs as APCs, and by synthesizing these NPs separately, a better control over particle growth, size and shape is possible. This topic is still ongoing research in our lab, and this brings us closer to the incorporation of these superconductors in high and alternating magnetic field applications, like in alternative energy generation.…”
Section: Applications High Temperature Yba2cu3o7-x Superconductorsmentioning
confidence: 99%
“…SrTiO 3 exhibits the perovskite crystal structure with a unit-cell parameter of a = 0.3905 nm and behaves as a semiconductor with a band gap of 3.2 eV . Due to the high charge storage capacity (i.e., dielectric constant), good insulating properties, chemical stability, and nontoxicity, the applications of STO thin films range from multifunctional devices such as high density capacitors, nonvolatile memories, and electro-optic components to buffer layers for superconducting coated conductors. These conductors generally consist of a textured or polycrystalline metallic substrate, a stack of textured buffer layers, and a superconducting YBa 2 Cu 3 O 7‑δ layer capped with a protective layer. , Titanate materials such as SrTiO 3 exhibit a small oxygen diffusion coefficient and a good chemical stability toward both the metallic substrate and the superconducting film, making these materials an interesting alternative for the commonly used buffer layers. , The current publication relates to the applicability of SrTiO 3 as a single buffer layer for obtaining optimal superconducting properties of YBa 2 Cu 3 O 7‑δ coatings, but the results will be generic in nature.…”
Section: Introductionmentioning
confidence: 99%
“…These buffer layers act as a template for transferring the bi-axial texture to the superconducting layer and form a diffusion barrier between the substrate and the superconducting lm avoiding oxidation of the substrate and contamination of the superconductor. For YBCO-based coated conductors, the deposition of many different potential buffer materials via CSD methods has been investigated, including SrTiO 3 , 7,8 CeO 2 9,10 and La 2 Zr 2 O 7 . [11][12][13] Until now, the best results have been obtained by using a double layered structure of LZO/CeO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The BaCeO 3 formation leads to problems regarding the texture and stoichiometry of the YBCO layer, leading to a signicant reduction in critical current densities. 10 To address this problem, alternative materials such as SrTiO 3 , 7,8 YBiO 3 (YBO) 16 and M x Ce 1Àx O 2+y 17,18 have been investigated to replace the currently used buffer stacks or the cerium oxide layer. Especially YBiO 3 shows very interesting characteristics and properties.…”
Section: Introductionmentioning
confidence: 99%